Physicochemical Characterisation of Polysaccharides from the Seeds and Leaves of Miracle Fruit (Synsepalum dulcificum) and Their Antioxidant and α-Glucosidase Inhibitory Activities In Vitro - Huajun Jian; Fang Qiao; Jie Chen; Nongyue He (Journal of Chemistry)
Miracle fruit (Synsepalum dulcificum) has been well known and studied for its unique taste-modifying ability. In this study, the monosaccharide composition, molecular weight (Mw), and in vitro bioactivities (antioxidant, α-glucosidase inhibition) of polysaccharides from the seeds (MFP-S) and leaves (MFP-L) of miracle fruit were investigated. The results showed that MFP-S was a homogeneous polysaccharide (Mw 2804 Da) with glucose. MFP-L displayed three fractions (92093, 1496, and 237 Da) consisting of rhamnose, arabinose, galactose, glucose, and xylose. Moreover, the antioxidant and α-glucosidase inhibition of MFP-L were significantly greater than those of MFP-S. The α-glucosidase inhibition of MFP-L was remarkably better than the positive control, acarbose (an antidiabetes drug). More specifically, the 50% inhibitory concentration (IC50) values of α-glucosidase activities for MFP-S, MFP-L, and acarbose were 33, 0.01, and 1 mg mL−1, separately. Therefore, MFP-L can be developed as a functional factor with both antioxidant and antidiabetes activities in food applications.